Influence of liver stiffness heterogeneity on staging fibrosis in patients with nonalcoholic fatty liver disease. Issue 1 (22nd February 2022) - Kawamura, Nobuyoshi; Imajo, Kento; Kalutkiewicz, Kyle J.; Nagai, Koki; Iwaki, Michihiro; Kobayashi, Takashi; Nogami, Asako; Honda, Yasushi; Kessoku, Takaomi; Ogawa, Yuji; Higurashi, Takuma; Hosono, Kunihiro; et al.
Abstract: Background and Aims: Despite that hepatic fibrosis often affects the liver globally, spatial distribution can be heterogeneous. This study aimed to investigate the effect of liver stiffness (LS) heterogeneity on concordance between MR elastography (MRE)‐based fibrosis staging and biopsy staging in patients with NAFLD. Approach and Results: We retrospectively evaluated data from 155 NAFLD patients who underwent liver biopsy and 3 Tesla MRE and undertook a retrospective validation study of 169 NAFLD patients at three hepatology centers. Heterogeneity of stiffness was assessed by measuring the range between minimum and maximum MRE‐based LS measurement (LSM). Variability of LSM was defined as the stiffness range divided by the maximum stiffness value. The cohort was divided into two groups (homogenous or heterogeneous), according to whether variability was below or above the average for the training cohort. Based on histopathology and receiver operating characteristic (ROC) analysis, optimum LSM thresholds were determined for MRE‐based fibrosis staging of stage 4 (4.43, kPa; AUROC, 0.89) and stage ≥3 (3.93, kPa; AUROC, 0.89). In total, 53 had LSM above the threshold for stage 4. Within this group, 30 had a biopsy stage of <4. In 86.7% of these discordant cases, variability of LSM was classified as heterogeneous. In MRE‐based LSM stage ≥3, 88.9% of discordant cases were classified as heterogeneous. Results of the validation cohort were similar to those of the training cohort. Conclusions: Discordance between biopsy‐ and MRE‐based fibrosis staging is associated with heterogeneity in LSM, as depicted with MRE.